Acute effects of static passive stretching without voluntary contraction of skeletal muscles on arterial stiffness in elderly lacking exercise habits - Takeshi Morifuji; Hidetoshi Nakao; Masashi Hashimoto; Masakazu Imaoka; Hidemi Fujino (Japanese Society of Physical Fitness and Sports Medicine, 2020)
Stretching exercises conducted by oneself, herein referred to as self-stretching exercises, improve arterial stiffness in healthy people. Such exercises include voluntary contraction of peripheral muscles in addition to stretching of target muscles. However, the effects of static passive stretching without voluntary contraction of skeletal muscles on arterial stiffness remain unknown. In addition, it is important to verify the effects of stretching in the elderly lacking exercise habits with advanced arterial stiffness. Therefore, the purpose of the present study was to verify the acute effects of static passive stretching, without voluntary contraction of skeletal muscles, on the cardio-ankle vascular index (CAVI) in elderly individuals lacking exercise habits. The present study followed a pretest-posttest design without a control group. Twenty-nine elderly individuals (mean age, 77.8 ± 7.0 years; 24 female) recruited at an orthopedic clinic participated in the present study. The participants were subjected to static passive stretching of the neck, trunk, and extremities for 40 min by the same physical therapist. Stretching involved the shoulder flexors/extensors, elbow flexors/extensors, wrist palmar flexors/dorsal flexors, hip flexors/extensors/adductors, knee flexors/extensors, ankle plantar flexors/dorsal flexors, neck muscles, and trunk muscles. The CAVI (Rt, Lt, Ave), ankle-brachial index (ABI), blood pressure, and pulse rate were assessed before and after stretching. After stretching, both CAVI (Lt, Ave) and pulse rate were significantly decreased. In contrast, no significant changes in CAVI (Rt), ABI, or blood pressure were observed. The key new finding of the present study was that static passive stretching without voluntary contraction of skeletal muscles acutely improved the CAVI in elderly individuals lacking exercise habits.